Ramadan fasting: does it good for normal, overweight and obese subjects? - Abu Bakar, Ibrahim (Asian Academic Research Associates, 2018)
This study was designed to evaluate the effect of Ramadan fasting on anthropometric, energy and macro & micro-nutrients intake changes of normal, overweight and obese subjects. A total of sixty seven volunteers aged between 19-24 years old were randomly recruited using convenience sampling method. The subjects were categorized to normal (BMI 18.5-24.9), overweight (BMI 25.0-29.9) and obese (BMI≥30). Their height, weight, waist and hip circumference as well as their body fat percentage were recorded on the first day and on the 21th day of Ramadan. Each subject was also asked to record his/her three days food intake, once during pre-fasting week and another was during the third week of Ramadan. The food intake data were then analysed using Malaysian Food Composition Table and Food Atlas. All data were analysed using statistical software SPSS 17.0. After 21 days of fasting, the results showed significant reduction (p<0.05) in body weight and waist-to-hip ratio of normal and overweight & obese subjects. BMI and body fat percentage in both normal and overweight & obese subjects were decreased but not significantly different at P>0.05. This study showed that Ramadan fasting give positive effects in term of body weight reduction of normal, overweight and obese subjects.